1983
DOI: 10.1002/pol.1983.170210623
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene degradation during combustion

Abstract: A novel driven‐rod, radiant pyrolysis technique has been used to study steady‐state linear regression of vertically mounted polystyrene rods degrading under high‐flux, nonflaming conditions that simulate those of combustion. With this technique a reliable, reproducible temperature‐depth profile (identical for combustion and radiant pyrolysis) for polystyrene has been obtained and used to successfully calculate the observed mass loss rate. Residues and volatiles have been analyzed. Mechanistic treatment of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
13
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 13 publications
6
13
0
Order By: Relevance
“…For all materials, most decomposition occurred in one single step, at temperatures between 630 and 755 K with the maximum weight change at between 707 and 722 K. This main decomposition process was attributed to the decomposition of HIPS. The results for the thermal decomposition of HIPS corresponded to those of comparable studies 19–21…”
Section: Resultssupporting
confidence: 76%
“…For all materials, most decomposition occurred in one single step, at temperatures between 630 and 755 K with the maximum weight change at between 707 and 722 K. This main decomposition process was attributed to the decomposition of HIPS. The results for the thermal decomposition of HIPS corresponded to those of comparable studies 19–21…”
Section: Resultssupporting
confidence: 76%
“…This finding accords with the literature [31]. It is concluded that a polymer pyrolysis occurs during the fire [32,33]. Apart from this anaerobic thermal decomposition hardly any thermo-oxidative processes are proved by comparing the residue masses for thermal analysis and fire.…”
Section: Morphology Of Hips/mg(oh) 2 /P R and Residue Massessupporting
confidence: 91%
“…This main decomposition process was attributed to the decomposition of HIPS. The results for the thermal decomposition of HIPS corresponded to those of comparable studies [14,15] .…”
Section: Thermal Decompositionsupporting
confidence: 79%